A Comparison of the Operative Techniques and the Postoperative Complications for Bone-Anchored Hearing Aid Implantation - Steehler, Mark W.; Larner, Sean P.; Mintz, Joshua S.; Steehler, Matthew K.; Lipman, Sidney P.; Griffith, Shane (International Archives of Otorhinolaryngology, 2018)
Introduction Bone anchored hearing aids (BAHA) represent a useful surgical option for patients with single sided deafness.Objectives To compare multiple techniques for BAHA implantation regarding postoperative complications, operative time, and duration between the surgery and the first use of the BAHA.Methods A retrospective study was conducted of all patients receiving implantation of a BAHA from August of 2008 to October of 2014. Data collected included: patient age, gender, side operated, abutment length, operative time, duration until first use of the BAHA, operative technique, and postoperative complications. The statistical analysis was performed using analysis of variance (ANOVA), Tukey pairwise comparison, chi-square, and paired t-test. Statistical significance was determined using a level of p < 0.05.Results A total of 88 patients (43 female and 45 male) were included in the data analysis. A total of 80 complications were documented, and these complications were classified according to the Holgers criteria. A significant difference in the total postoperative complications existed between the six techniques used (ANOVA; p < 0.01). In addition, there was also a significant difference among the six techniques employed regarding the operative time (ANOVA; p < 0.01). The average time duration until fitting of the BAHA processor among the various techniques trended toward but did not reach statistical significance (ANOVA; p = 0.16).Conclusions Significant differences in the operative outcomes exist among the various techniques for BAHA implantation. Based on the statistical analysis of our data, the BAHA Attract system (Cochlear Ltd., Sidney, Australia) requires greater operative time, but it is associated with less postoperative complications than percutaneous techniques and its processor may be fitted significantly sooner.
Keywords: hearing aids; deafness; otologic surgical procedures